Computational Design, Synthesis, and Photochemistry of Cy7‐PPG, an Efficient NIR‐Activated Photolabile Protecting Group for Therapeutic Applications. (10th March 2022) - Alachouzos, Georgios; Schulte, Albert M.; Mondal, Anirban; Szymanski, Wiktor; Feringa, Ben L.
Abstract: Photolabile Protecting Groups (PPGs) are molecular tools used, for example, in photopharmacology for the activation of drugs with light, enabling spatiotemporal control over their potency. Yet, red‐shifting of PPG activation wavelengths into the NIR range, which penetrates the deepest in tissue, has often yielded inefficient or insoluble molecules, hindering the use of PPGs in the clinic. To solve this problem, we report herein a novel concept in PPG design, by transforming clinically‐applied NIR‐dyes with suitable molecular orbital configurations into new NIR‐PPGs using computational approaches. Using this method, we demonstrate how Cy7, a class of NIR dyes possessing ideal properties (NIR‐absorption, high molecular absorptivity, excellent aqueous solubility) can be successfully converted into Cy7‐PPG. We report a facile synthesis towards Cy7‐PPG from accessible precursors and confirm its excellent properties as the most redshifted oxygen‐independent NIR‐PPG to date (λmax =746 nm). Abstract : The computational design and synthesis of Cy7‐PPG, a new oxygen‐independent novel near‐infrared photolabile protecting group (PPG) is reported. Cy7‐PPG is the most redshifted PPG to date (λmax =746 nm), with unmatched near‐infrared molecular absorptivity and aqueous solubility, and excellent uncaging efficiency, paving the way for the use of PPGs in the clinic.